Особливості фізіолого-біохімічних процесів у листках Populus bolleana Lauche, Ulmus pinnato-ramosa Dieck. та Elaeagnus angustifolia L. в умовах промислового забруднення середовища - Levon, F.M.; Julavska, G.P. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 1999)
The complex research of physiological-biochemical processes of the woody plants of Ulmus pinnato-ramosa Dieck, Elaeagnus angustifolia L. and Populus boleana Lauche in the polluted environment of the ferrous metallurgy plants have been carried out with results presented. A stable state of the pigmentary systems has been marked for U. pinnato-ramnosa high content of green pigment, their fraction bound with proteinaceous-lipoid complex that positively correlates with the degree of water ordering, in particular. In the leaves of E. angustifolia quantity of pigments and their fraction bound with protein almost did not change. The water structurization increased at the expense of the less ardered and the most ordered water. In the leaves of P. boleana the content of pigments and chlorophyll fraction closely bound to protein had no definite tendency, depending on the environment. The prospects of U. pinnato-ramosa and E. angustifolia use for gardening in conditions of high pollution of the environment is made sure. High individual adaptability of the above plans to conditions of man-caused transformed environment been certified.